2022
DOI: 10.1007/s00415-022-11190-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes of T lymphocyte subpopulations and their roles in predicting the risk of Parkinson’s disease

Abstract: T lymphocytes are involved in the pathogenesis of Parkinson’s disease (PD), while the heterogeneity of T-cell subpopulations remains elusive. In this study, we analyzed up to 22 subpopulations of T lymphocytes in 115 PD patients and 60 matched healthy controls (HC) using flow cytometry. We found that PD patients exhibited decreased naïve CD8+ T cells (CD3+ CD8+ CD45RA+ CD45RO−) and increased late-differentiated CD4+ T cells (CD3+ CD4+ CD28− CD27−), compared to HC, which were not affected by anti-parkinsonism m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…For example, our nding that activation of puri ed CD4 + T cells is signi cantly reduced by NDEs from A53T-syn models may offer a mechanism underlying disease progression since a reduction of activated CD4 + T cells has been associated with the advancement of PD [10,11,49]. Our nding that A53T-syn Exo suppresses both naïve and matured CD8 + T supports previous studies reporting decreases of naïve CD8 + T cells and cytotoxic CD8 + T cells in PD [9,49,50]. Several studies have noted a decrease of Th1 cells and Th1-promoting transcription factors including T-bet, STAT3, and STAT4 in PD patients [14,51], which is consistent with our nding that A53T-syn NDEs reduce T-bet level and suppress Th1 differentiation.…”
Section: Discussionsupporting
confidence: 87%
“…For example, our nding that activation of puri ed CD4 + T cells is signi cantly reduced by NDEs from A53T-syn models may offer a mechanism underlying disease progression since a reduction of activated CD4 + T cells has been associated with the advancement of PD [10,11,49]. Our nding that A53T-syn Exo suppresses both naïve and matured CD8 + T supports previous studies reporting decreases of naïve CD8 + T cells and cytotoxic CD8 + T cells in PD [9,49,50]. Several studies have noted a decrease of Th1 cells and Th1-promoting transcription factors including T-bet, STAT3, and STAT4 in PD patients [14,51], which is consistent with our nding that A53T-syn NDEs reduce T-bet level and suppress Th1 differentiation.…”
Section: Discussionsupporting
confidence: 87%
“…In conclusion, our findings increase the fundamental understanding of how GLD pathology occurs and suggest salient insights that may support novel therapeutic approaches to treat GLD. Furthermore, these data have potential relevance for other neurological diseases in which CD8 + T cells have been implicated, yet their origins remain enigmatic, such as Alzheimer’s disease ( Altendorfer et al, 2022 ; Gate et al, 2020 ), Parkinson’s disease ( Williams-Gray et al, 2018 ; He et al, 2022 ), or amyotrophic lateral sclerosis ( Campisi et al, 2022 ; Rentzos et al, 2012 ). Hence, we propose that the development of CD8 + T cells in this model represents a unique opportunity to study the natural development of CD8 + T cell responses that appear to target the CNS.…”
Section: Resultsmentioning
confidence: 98%
“…Similar to AD, many studies have reported an alteration in T lymphocytes in the peripheral blood (PBs) and CSF of PD patients (Baba et al, 2005;He et al, 2022;Heming et al, 2022). Early studies showed an increased or decreased ratio of CD4 to CD8 + T cells in the PBs and CSF of PD patients (Hisanaga et al, 2001;Baba et al, 2005).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 98%
“…PD Infiltration PB or CSF of PD patients: CD4 to CD8 ratio changes (He et al, 2022;Fu et al, 2023); decreased number (Baek et al, 2016); CD8 + T cell terminal effector phenotype (Marsh et al, 2016), with high expression of TNFα Heming et al, 2022) and show immunosenescence (Hisanaga et al, 2001;Chen et al, 2021). Brain tissue of PD patients: significant infiltration in the SN (Williams-Gray et al, 2018;Kouli et al, 2021;Jiang et al, 2023).…”
Section: Ad Infiltrationmentioning
confidence: 99%
See 1 more Smart Citation